Apatite Fission Track Thermochronology of Granite from Duobaoshan Porphyry Cu (Mo) Deposit, Northeast China: Implications for Cooling History and Ore Preservation. (8th March 2022) - Leng, Yaxing; Wang, Jianping; Zheng, Dewen
Abstract : The Duobaoshan Cu (Mo) deposit is one of the oldest super large porphyry deposits in the eastern part of the Central Asian orogenic belt. Although ore-forming processes have been extensively concerned, the post-mineralization ore preservation state was poorly focused on. In order to improve the ability of prospecting forecast, it is necessary to consider both deposit formation and deposit preservation. Here, we reported apatite fission track (AFT) data for the Duobaoshan porphyry copper deposits in the belt to reveal the cooling and exhumation history and evaluate ore preservation. The results show that the rapid cooling of the ore-hosting rock body occurred later than the surrounding rock body. The rapid cooling of the surrounding granodiorite occurred between 82 and 72 Ma, with the exhumation depth of 2.33–3.11 km and the exhumation rate of 0.25 mm/a, whereas the ore-hosting granodiorite porphyry was rapid cooling between 71.8 and 50.2 Ma, with the exhumation depth of 2.99–3.86 km and the exhumation rate of 0.22 mm/a. This differential exhumation and cooling event provide favorable geological conditions for the preservation of the ore body.